Firm-specific and Contextual Determinants of Sri Lankan Corporate Hotel Performance - Weerathunga, Prageeth Roshan; Xiaofang, Chen; Samarathunga, Manoj (International Journal of Economics and Financial Issues, 2019)
Stimulated by the burgeoning tourism industry and its vital importance to the country's economy, this study examines the firm-specific and contextual determinants of Sri Lankan corporate hotel performance. We use data from a sample of 29 listed hotels for seven years from 2012 to 2018. This study uses a multidimensional financial performance measure (CFPS), in addition to return on assets (ROA) and return on equity (ROE). Consequently, the results from the panel regression revealed that hotels' age and size are negatively and significantly affect financial performance. Furthermore, the results suggest that the profitability of Sri Lankan hotels is driven by managerial efficiency, Location factors, geographical diversification, and connection to a wider business network. Keywords: Firm Performance, Determinants, Corporate Hotels JEL Classifications: M410, M210, M370, L1 DOI: https://doi.org/10.32479/ijefi.7880